Characteristics and secondary transformation potential of volatile organic compounds in Wuhan, China. (1st February 2023) - Zhang, Yujun; Li, Feng; Cheng, Qiang; Zhang, Chen; Liu, Yafei; Li, Qijie; Yin, Shijie; Zhang, Siqing; Liu, Xingang
Abstract: In this study, comprehensive field observations were collected out in urban, suburban and industrial areas of Wuhan, China in winter to compare and analyse the concentration level, source and secondary transformation potential of volatile organic compounds (VOCs). And the CJZ, SLDD and HGQ sites were used to assess the atmospheric VOC pollution in urban, suburban and industrial areas respectively. The total VOC (TVOC) concentrations at the three sites were 25.35 ± 12.66, 28.55 ± 9.19 and 66.81 ± 65.40 ppb, respectively, which shows that pollution in the industrial area is more serious. Vehicle exhaust and industrial emissions are the main sources of VOC emissions in Wuhan. The contributions of vehicle exhaust and industrial emissions to the VOCs are 57.03%, 48.44% and 55.18% at the CJZ, SLDD and HGQ sites, respectively. High potential source contribution function values mainly occur in the east and southwest areas of the sampling sites, indicating that Wuhan has a strong local VOC source. In addition, alkenes and aromatics play a leading role in secondary conversion during selected periods of relatively high O3 concentration. At the same time, the simulation results of the F0AM model fall within the VOC-limited regimes, and the suburban and industrial area are more sensitive to VOCs. The O3 concentration can be effectively reduced when the reduction ratio of AVOCs/NOx is 1.25–1.56, 1.11–1.20 and 1.42–1.61. In general, it is imperative to reduce VOC emissions by region and implement active VOC-species-focused strategies. Graphical abstract: Image 1 Highlights: The TVOC concentration in the industrial area was 2–3 times higher than that in the urban and suburban areas. Different functional areas had distinct chemical features in atmosphere. Emissions from industrial areas had a significant transmission impact on urban areas. Alkenes and aromatics played a dominant role in secondary transformation. Industrial areas had a higher reduction ratio of AVOCs/NOx.